KONSTRUKSI BUDAYA AKIKAH DAN SÊLAPAN: STUDI LIVING QUR’AN DI KABUPATEN PROBOLINGGO - Basid, Abd; Romziana, Luthviyah; Sholeha, Iklimatus (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2021)
This study aims to describe how the culture of akikah and sêlapan in society in Probolinggo Regency. As a new study in this culture, the living Qur'an is a scientific research that we do, related to the presence of the Qur'an in a certain Muslim community. With a descriptive-phenomenological method that aims to provide an understanding of how the culture is in Probolinggo Regency and examine several aspects 1) How is the implementation of akikah and sêlapan culture in Probolinggo Regency; and 2) Connecting the culture with the Qur'an and interpretation. The results of the study show that this culture is a hereditary culture carried out by the community and each procession has its own meaning, one of the meanings contained in this procession is that the community believes that this culture is a form of belief that the implementation of akikah and sêlapan will bring blessings to life for the child.